Heparin-Binding Epidermal-like Growth Factor (HB-EGF) Reduces Cell Death in an Organoid Model of Retinal Damage - Michelle N. H. Tang; Mariya Moosajee; Najam A. Sharif; G. Astrid Limb; Karen Eastlake (Organoids, 2024)
In zebrafish and various mammalian species, HB-EGF has been shown to promote Müller glia proliferation and activation of repair mechanisms that have not been fully investigated in human retina. In the current study, 70- to 90-day-old human retinal organoids were treated with 20 μM 4-hydroxytamoxifen (4-OHT), and CRX, REC, NRL, PAX6, VIM, GFAP, and VSX2 gene and protein expression were assessed at various times points after treatment. Organoids with or without 4-OHT-induced damage were then cultured with HB-EGF for 7 days. We showed that 20 μM 4-OHT caused a reduction in the number of recoverin-positive cells; an increase in the number of TUNEL-positive cells; and downregulation of the photoreceptor gene markers CRX, NRL, and REC. Culture of organoids with HB-EGF for 7 days after 4-OHT-induced damage caused a marked reduction in the number of TUNEL-positive cells and small increases in the number of Ki67-positive cells and PAX6 and NOTCH1 gene expression. The current results suggest that treatment of human ESC-derived retinal organoids with 4-OHT may be used as a model of retinal degeneration in vitro. Furthermore, HB-EGF treatment of human retinal organoids increases proliferating Müller cells, but only after 4-OHT induced damage, and may be an indication of Muller reactivity in response to photoreceptor damage. Further studies will aim to identify factors that may induce Müller cell-mediated regeneration of the human retina, aiding in the development of therapies for retinal degeneration.